Bogolyubov averaging and normalization procedures in nonlinear mechanics. II - Lopatin, A. K.; Mitropolskiy, Yu. A. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
By using a new method suggested in the first part of the present work, we study systems which become linear in the zero approximation and have perturbations in the form of polynomials. This class of systems has numerous applications. The following fact is even more important: Our technique demonstrates how to generalize the classical method of Poincaré-Birkhoff normal forms and obtain new results by using group-theoretic methods. After a short exposition of the general theory of the method of asymptotic decomposition, we illustrate the new normalization technique as applied to models based on the Lotka-Volterra equations.